Oral health status and practices of 6- to 7-year-old children in Amman, Jordan: a cross-sectional study - Ahmad Aljafari; Rawan ElKarmi; Osama Nasser; Ala'a Atef; Marie Therese Hosey (BMC, 2022)
Abstract Background Dental caries affects the majority of children in Jordan, with some evidence of its prevalence steadily increasing. Previous studies have shown that families struggle to establish good oral health practices. The aim of this study was to evaluate the current oral health status and practices of 6- to7-year-old children in Amman, Jordan.r Methods A cross-sectional cohort study. The sample consisted of 6- to 7-year-old children attending six randomly selected schools in Amman, Jordan. Measures collected were: I) Caries experience (d3mft/D3MFT), II) Oral hygiene, measured using the Simplified Oral Hygiene Index, III) Dietary, toothbrushing, and dental attendance practices, measured using diaries and parental questionnaires, IV) Participants' basic characteristics: age, education and employment. Data were analysed using SPSS20. Results In total, 942 children were recruited. Four hundred and fifty-seven were boys, 485 were girls. Their average age was 6.5 years. Eighty-nine percent had decay in their primary teeth. Mean d3mft was 5.1(1 (range = 0-12, SD = 2.9). Only 8% of carious teeth were restored. Mean DMFT score was 0.3 (range = 0-4, SD = 0.8). Mean debris score was 1.07 (range = 0-3, SD = 0.37). Children indicated that they brush their teeth 1.6 times a day (range = 0-3, SD = 0.6). The majority (81%) were unsupervised. Sixty-seven percent of parents did not know the appropriate fluoride toothpaste concentration. Children were having 1.5 sugary snacks in-between their meals (Range = 1-6, SD = 1.1). They scored a mean of 2.5 (Range = 0-5.87, SD = 1.7) in sweetened drinks intake (recommended ≤ 1) and 2.8 (Range = 0-18.57, SD = 1.5) in non-core food intake (recommended ≤ 2) on a dietary questionnaire. Most parents (84%) indicated that their child attends the dentist only when in pain, and 18% indicated that their child is extremely afraid of dentists. Only 32% and 18% were familiar with fluoride varnish and fissure sealants, respectively. Regression analysis revealed that debris score and dental attendance were reliable predictors of caries experience. Conclusions Six- to seven-year-old children in Amman, Jordan have a high caries experience. Most show signs of poor oral hygiene, excessive intake of cariogenic foods, and symptomatic dental attendance. Their parents lack knowledge on fluoride varnish and fissure sealants. There is a need for oral health promotion tailored to this cohort's need.